2008
DOI: 10.1055/s-2007-963614
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkung propriozeptiver Trainingsgeräte auf beteiligte Muskulatur im Einbeinstand

Abstract: Today in each therapy and training program proprioceptive exercises are integrated. A lot of equipment you can buy. But for an more effective training exercises and equipment should be select more regarding the aim and the problem of the training. In literature is not much written about the specific way proprioction equipment stimulate different muscles. In this study 15 students of sport sciences (25.7 +/- 2.2 years, 8 male, 7 female) were tested for a period of 15 seconds in a single-leg standing position on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 4 publications
4
8
0
1
Order By: Relevance
“…First and quite similarly than CoP, the smaller the board bases, the higher the muscular participation. Such conclusion has previously been obtained [9]. But, as for CoP variability, we are surprised to detect high EMG activity for both TA and SOL muscles in FREEMAN as well as in LATERAL boards.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…First and quite similarly than CoP, the smaller the board bases, the higher the muscular participation. Such conclusion has previously been obtained [9]. But, as for CoP variability, we are surprised to detect high EMG activity for both TA and SOL muscles in FREEMAN as well as in LATERAL boards.…”
Section: Discussionsupporting
confidence: 84%
“…Let's remember that this latter exclusively allowed mediolateral displacements while TA and SOL act in anteroposterior direction. Quite similarly, Dohm-Acker et al [9] previously registered the highest EMG activity in TA, PL and gastrocnemius muscles. Also, Braun Ferreira et al [1] found high EMG activity in TA (in association with PL) on trampolines and force platforms.…”
Section: Discussionmentioning
confidence: 52%
“…Further, studies investigated the effects of increasing BTD on neuromuscular activity. Results showed that lower limb muscle activity (Dohm-Acker et al, 2008; Cimadoro et al, 2013) and coactivation (Donath et al, 2016) increased with increasing BTD. In fact, recent studies on the progression of BTD were mainly conducted using various environmental conditions to manipulate posture (e.g., BoS, training device, surface, vision, etc.)…”
Section: Introductionmentioning
confidence: 96%
“…Probanden, die ihre Vorerfahrung "hoch" oder "sehr hoch" einschätzen, weisen ein geringeres Wegsignal auf als Probanden, die ihre Vorerfahrung als "gering" oder "mittel" bezeichnen. Die Verbesserung der Werte auf dem Posturomed nach Trainingsintervention ist bekannt[16,17], sodass die Hypothese des positiven Einflusses bestimmter Sportarten, die Einbeinstand oder gute Gleichgewichtsfähigkeit auf einem Bein fordern, nahe liegt. Dies hat sich auch in den Messwerten bestätigt.…”
unclassified